2019
DOI: 10.3847/1538-3881/ab245e
|View full text |Cite
|
Sign up to set email alerts
|

New Substellar Discoveries from Kepler and K2: Is There a Brown Dwarf Desert?

Abstract: We present the discoveries of a brown dwarf and a low mass star from the Kepler and K2 missions. The newly discovered brown dwarf is EPIC 212036875b and the low mass star is KOI-607b. EPIC 212036875b has a mass of M b = 52.3 ± 1.9 M J , a radius of R b = 0.874 ± 0.017 R J , and orbits its host star in P = 5.169885 ± 0.000027 days. Its host star is a late F-type star with M = 1.288 ± 0.065 M , R = 1.498 ± 0.025 R , and T eff = 6238 ± 60K. KOI-607b has a mass of M b = 95.1 ± 3.4 M J , a radius of R b = 1.089 ± 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Thanks to the evolutionary state of the host star, this is one of the few transiting brown dwarfs for which a relatively precise age can be estimated. Our results are in agreement with Carmichael et al (2019) who recently reported an independent discovery and characterisation of EPIC 212036875 b.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Thanks to the evolutionary state of the host star, this is one of the few transiting brown dwarfs for which a relatively precise age can be estimated. Our results are in agreement with Carmichael et al (2019) who recently reported an independent discovery and characterisation of EPIC 212036875 b.…”
Section: Discussionsupporting
confidence: 94%
“…These values are longer than the system age, and hence the BD's orbit will not be currently tidally evolving. We note that the pre-print of Carmichael et al (2019) gives a slightly longer circularisation time of 47 Gyr. The difference is largely due to their considering only the tide raised on the brown dwarf.…”
Section: Tidal Evolution Of the Systemmentioning
confidence: 74%
See 3 more Smart Citations